Influence of Parenting Patterns and Self-Efficacy on the Leadership of Cadet Regiment at Merchant Marine Polytechnic of West Sumatera - Irwan, Irwan; Putra, Riki Wanda; Erlinda, Nelfi; Andini, Nisye Frisca (Universitas Muhammadiyah Yogyakarta, 2024)
This research was conducted due to the problem of cadets' leadership, which is still not perfect. The cadets' leadership is assumed to be influenced by parenting patterns from the institution and their self-efficacy. This research aims to describe the influence of parenting patterns and self-efficacy on the leadership of the cadet regiment. This quantitative research applied ex post facto methods. The population was the cadets of Batch VII and VIII at Merchant Marine Polytechnic of West Sumatera. Accordingly, the research sample used a probability sampling technique with proportionate stratified random sampling by using the Slovin formula. The total sample of this research was 191 cadets, while the instrumentation was a questionnaire about parenting patterns, self-efficacy, and leadership. The data collection technique involved giving a questionnaire directly to the sample. The data analysis technique used multiple linear regression analysis by using the SPSS application. The results showed that Hypotheses 1, 2, and 3 were accepted, which means parenting patterns and self-efficacy influenced the leadership of the cadet regiment, and there is an influence of self-efficacy and parenting patterns simultaneously on the leadership of the cadet regiment. The relevant practical implication of this research focused on both internal stakeholders, namely the lecturers or officers and the cadets of Merchant Marine Polytechnic of West Sumatera. Therefore, it is recommended that the director and management pay attention to the parenting patterns and the cadets pay attention to their self-efficacy in order to develop better leadership of the cadet regiment.